Editorial: Spatial dependency, spillovers and farm efficiency - Areal, Francisco J.; Pede, Valerien O. (Frontiers Media, 2022)
To enhance sustainable agricultural production and land-use governance, a good understanding of the drivers behind farm-level production efficiency is required. Although spatial aspects such as climate, soil, altitude, culture, and infrastructure may well be correlated with farm production, these are rarely accounted for in efficiency analysis. Not accounting for such factors may lead to biased farm-level efficiency estimates. Spatial characteristics, both observed and unobserved by researchers, should be incorporated into efficiency analysis to provide robust advice to multi-level governance. Indeed, not accounting for such spatial heterogeneities may lead to biased results and misleading recommendations to policymakers, extension agents, farmers, and land managers.